Implementation of Sharia Compliance in Murabahah Financing Contracts in Sharia Banking in West Sulawesi (Study on Bank Muamalat Indonesia West Sulawesi) - Ahsan Abdissalam; Muliati; Damirah (Universitas Muhammadiyah Palu, 2025)
This research discusses the Implementation of Sharia Compliance in Murabahah Financing Agreements in Sharia Banking in West Sulawesi (Study at Bank Muamalat Indonesia, West Sulawesi). The formulation of the problem in this research is: 1.) What is the mechanism for murabahah contracts at Bank Muamalat Indonesia in Sulawesi West, 2.) What is the review of Sharia principles regarding the implementation of the Murabahah Agreement at Bank Muamalat Indonesia in West Sulawesi. The research method uses a qualitative type of research. The research approach used is case study research or case study, which is a type of research in which the data analysis process is carried out in depth on a case object in the research, where the unit of analysis is individual. data collection tools, namely interview guidelines; data collection techniques are observation, interviews and documentation; and testing the validity of the data using triangulation techniques. Research results: the buying and selling model carried out is guided by the murabahah scheme as it should be, when the customer wants to buy a house and the initial payment has been made, the bank will budget the estimated costs. The bank will buy the house according to the price shortfall from the payment made at the beginning. If the house price is Rp. 120 million and initial payment of Rp. 20 million as a receipt for becoming a customer with the developer, then the bank will buy the house for Rp. 100 million. So the basic price of the house that is resold to the customer is IDR. 100 million plus the profit margin from sales made by the bank to customers. The concept of buying and selling carried out by the Bank is a buying and selling concept that is in accordance with the rules for implementing the murabahah contract. Where there is a sale and purchase transaction carried out by the bank, supplier and customer involving the object of the contract, then a Cost Budget Plan (RAB) will be made according to the customer's needs for the object of the goods and a purchase receipt will be requested directly by the Bank.